2015
DOI: 10.1093/mnras/stu2668
|View full text |Cite
|
Sign up to set email alerts
|

The reionization of carbon

Abstract: Observations suggest that C II was more abundant than C IV in the intergalactic medium towards the end of the hydrogen reionization epoch (z ∼ 6). This transition provides a unique opportunity to study the enrichment history of intergalactic gas and the growth of the ionizing background (UVB) at early times. We study how carbon absorption evolves from z = 10-5 using a cosmological hydrodynamic simulation that includes a self-consistent multifrequency UVB as well as a well-constrained model for galactic outflow… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
109
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(124 citation statements)
references
References 74 publications
11
109
4
Order By: Relevance
“…Based on a robust statistical analysis on full CMB spectrum and quasar data and using the observations of high-z galaxy LFs, we (Mitra et al 2013) derived that mean value of fesc is moderately increasing from 7% at z = 6 to 18% at z = 8. This increasing behavior of fesc on redshift is somewhat similar to that obtained or assumed in Inoue et al (2006); Razoumov & Sommer-Larsen (2010); Haardt & Madau (2011 ;Ferrara & Loeb (2013);Finlator et al (2015). More recently, using a high-resolution cosmological zoom-in simulation of galaxy formation, Ma et al (2015) found a considerably lower (< 5%; much less than required by reionization models) and a non-evolving escape fraction.…”
Section: Introductionsupporting
confidence: 85%
“…Based on a robust statistical analysis on full CMB spectrum and quasar data and using the observations of high-z galaxy LFs, we (Mitra et al 2013) derived that mean value of fesc is moderately increasing from 7% at z = 6 to 18% at z = 8. This increasing behavior of fesc on redshift is somewhat similar to that obtained or assumed in Inoue et al (2006); Razoumov & Sommer-Larsen (2010); Haardt & Madau (2011 ;Ferrara & Loeb (2013);Finlator et al (2015). More recently, using a high-resolution cosmological zoom-in simulation of galaxy formation, Ma et al (2015) found a considerably lower (< 5%; much less than required by reionization models) and a non-evolving escape fraction.…”
Section: Introductionsupporting
confidence: 85%
“…The impact of radiative feedback is less important in the CROC simulations than in CoDa. Finlator et al (2015Finlator et al ( , 2016Finlator et al ( , 2017: the Finlator et al (2015Finlator et al ( , 2016Finlator et al ( , 2017 LF results are based on a cosmological simulation of galaxy formation in a h 7.5 1 3 -( ) Mpc 3 volume of the universe including both gravity and hydrodynamics as implemented in the GADGET-3 code (Springel 2005). To this code, gas cooling is added through collisional excitation of hydrogen and helium as in Katz et al (1996), and metal line cooling is implemented using the collisional ionization equilibrium tables of Sutherland & Dopita (1993).…”
Section: Comparison With Theoretical Expectationsmentioning
confidence: 99%
“…Star formation is added using the Kennicutt-Schmidt law, with supernovae feedback included following the "ezw" prescription from Davé et al (2013) and metal enrichment from supernovae as implemented as in Oppenheimer & Davé (2008). Flattening in the Finlator et al (2015Finlator et al ( , 2016Finlator et al ( , 2017 LFs occurs mostly due to less efficient gas cooling at lower halo masses.…”
Section: Comparison With Theoretical Expectationsmentioning
confidence: 99%
“…This in turn is important for the temperature state of the intergalactic medium (Ciardi et al 2012). Another example is the modelling of carbon absorption systems during reionization, in which a frequency-dependent escape fraction could play an important role for modelling the ratio of C II to C IV (Finlator et al 2014). …”
Section: The Spectrum Of Outgoing Radiationmentioning
confidence: 99%